2020
DOI: 10.1055/s-0040-1715473
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Pathogenesis, Risk Factors, and Treatment of Portal Vein Thrombosis in Patients with Cirrhosis

Abstract: Portal vein thrombosis (PVT) is a frequent event in patients with cirrhosis regardless of etiology. Notwithstanding the commonality of the problem, the pathophysiology and risk factors for PVT in cirrhosis are largely unknown. The clinical impact of PVT in the natural history of cirrhosis is unclear, indications for PVT treatment are not well defined, and treatment recommendations are based on experts' opinion and consensus only. Therefore, this review aims to summarize current knowledge of mechanisms and risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 85 publications
0
21
0
1
Order By: Relevance
“…The pathogenesis of a thrombus is generally multifactorial and it is believed that its occurrence is mainly determined by the interrelation of the three physiological factors of Virchow's triad: the hypercoagulability of the blood, the stasis of blood flow, and intravascular vessel wall damage [24,25]. Nevertheless, the exact contribution of each of these factors to PVT development has not been fully elucidated [26,27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenesis of a thrombus is generally multifactorial and it is believed that its occurrence is mainly determined by the interrelation of the three physiological factors of Virchow's triad: the hypercoagulability of the blood, the stasis of blood flow, and intravascular vessel wall damage [24,25]. Nevertheless, the exact contribution of each of these factors to PVT development has not been fully elucidated [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…In this review, we aim to incorporate the latest studies on PVT development in the context of cirrhosis with the existent knowledge, as well as discuss all three vertices of Virchow's triad in detail and propose future directions for the advancement of this field. Both the clinical management of PVT and the invasion of the portal vein due to HCC, which have been reviewed elsewhere [27,28], are out of the scope of this review.…”
Section: Introductionmentioning
confidence: 99%
“…Es gilt abzuwägen, ob diese Möglichkeiten aufgrund der schweren Leberdysfunktion mit kon-sekutiverBlutungsdiathese oderaberaufgrund des schlechten Allgemeinzustands eines Patienten mit fortgeschrittener Leberzirrhose nicht mehr zur Verfügung stehen. Auch die Möglichkeiten der Antikoagulation können bei diesen Patienten nicht immer komplett ausgeschöpft werden [2,3].…”
Section: Leberdysfunktion Kann Die Therapeutischen Möglichkeiten Beeiunclassified
“…In these studies, PVT appears to be a marker of cirrhosis severity, which is a confounder that predominantly determines disease progression. 76 However, these studies included very few patients who had complete PVT. It was reported that four of eight patients with complete PVT experiencing spontaneous improvement, at rates similar to those with non-complete PVT.…”
Section: Asymptomatic Pvt In Non-transplant Candidatesmentioning
confidence: 99%